Nonisothermal Desorption of the Libr Aqueous Salt Solution in Minichannels - Misyura S.Y. (MATEC Web of Conferences, 2015)
This work is devoted the research for two (three)-phase flows of LiBr water solution in minichannels with different heat flux and wall thicknesses. Six flow patterns have been observed: a bubble flow, plug flow, laminar and oscillating laminar flow, mist flow, and flow locking. The physical solution properties and the equilibrium conditions change in time. The desorption rate depends not only on the heat flow and speed ratio of vapor to liquid, but also on the total area of the interface (liquid-vapor). The third phase (solid crystal hydrates) are formed under high heat fluxes and in the presence of boiling crisis. A variation in the wall thickness leads to a change in the desorption mode. With increasing wall thickness the boiling crisis is realized at higher heat fluxes.